Costs of the 'Hartslag Limburg' community heart health intervention - Ruland Erik; Steenbakkers Mieke; Groot Wim; Ronckers Emma T; Ament Andre (BMC, 2006)
Abstract Background Little is known about the costs of community programmes to prevent cardiovascular diseases. The present study calculated the economic costs of all interventions within a Dutch community programme called Hartslag Limburg, in such a way as to facilitate generalisation to other countries. It also calculated the difference between the economic costs and the costs incurred by the coordinating institution. Methods Hartslag Limburg was a large-scale community programme that consisted of many interventions to prevent cardiovascular diseases. The target population consisted of all inhabitants of the region (n = 180.000). Special attention was paid to reach persons with a low socio-economic status. Costs were calculated using the guidelines for economic evaluation in health care. An overview of the material and staffing input involved was drawn up for every single intervention, and volume components were attached to each intervention component. These data were gathered during to the implementation of the intervention. Finally, the input was valued, using Dutch price levels for 2004. Results The economic costs of the interventions that were implemented within the five-year community programme (n = 180,000) were calculated to be about €900,000. €555,000 was spent on interventions to change people's exercise patterns, €250,000 on improving nutrition, €50,000 on smoking cessation, and €45,000 on lifestyle in general. The coordinating agency contributed about 10% to the costs of the interventions. Other institutions that were part of the programme's network and external subsidy providers contributed the other 90% of the costs. Conclusion The current study calculated the costs of a community programme in a detailed and systematic way, allowing the costs to be easily adapted to other countries and regions. The study further showed that the difference between economic costs and the costs incurred by the coordinating agency can be very large. Cost sharing was facilitated by the unique approach used in the Hartslag Limburg programme.